The institutional determinants of political transactions - Carlos Scartascini (Inter-American Development Bank, Research Department, 2007)
Public policies are the outcome of the interaction among a variety of key political actors, each with its own preferences and incentives, who meet in different arenas and interact within the constraints of the institutions that frame their engagement. Therefore, to recognize the reasons behind the success or failure of any public policy it is necessary to understand the country's political institutions and the policymaking process they in turn help shape. This document looks at a number of those key actors, institutions, and arenas, with the aim of examining the roles, incentives, and capabilities of each of the actors in the policymaking process, by drawing from an extensive literature in political science and political economy. Each of the actors is looked at individually but connected to the other actors by linking the impact of political institutions on their incentives to the features of the policymaking game. Hopefully, this document will provide researchers with the tools necessary to embark in the fascinating analysis of policymaking processes not only for Latin American countries but also for other parts of the world.
Keywords: 330